Growth in representation of Saudi scientists among Stanford's top 2 percent most-cited (2019–2023) - Altukhaifi, Luluah; Alturaiki, Nouf; Al-hadyan, Khaled (Frontiers in Research Metrics and Analytics, 2025)
Global citation-based databases, such as Stanford University's Top 2% Scientists (SUD2%) database, offer powerful tools for tracking high-impact researchers. Despite Saudi Arabia's growing investment in scientific research, a longitudinal analysis of its presence in these elite citation rankings has been lacking. This study provides the first 5-year analysis (2019–2023) of Saudi-affiliated scientists listed in the SUD2% (single-year category), evaluating their growth in numbers, performance indicators, disciplinary distribution, and gender representation. Data were extracted from Elsevier's Mendeley-hosted SUD2% dataset. The key bibliometric metrics under analysis included the average composite citation score (C-score), citation rank, total citations, and h-index. A one-way repeated measures ANOVA on ranks was used to assess statistical differences between Saudi-affiliated and global scientists. Gender classification was performed using NamSor, based on validated confidence thresholds. The number of Saudi-affiliated scientists in the SUD2% nearly tripled from 556 in 2019 to 1,684 in 2023. Significant gains were also observed in average C-scores (p = 0.003), citation ranks (p = 0.002), total citations (p = 0.001), and h-indices (p = 0.025). Disciplinary analysis revealed continued dominance in clinical medicine, chemistry, and biomedical research. Gender analysis revealed male dominance (93.9%) over the 5-year period, although female representation increased from 5.0% in 2019 to 7.3% in 2023. Saudi Arabia's scientific community is making statistically significant progress in high-impact research, evidenced by increasing representation and improved citation metrics in global SUD2% rankings. While gaps remain—particularly in gender representation and individual citation ranks—trends point toward sustained momentum and broadening institutional participation in global research excellence.